Exploring the use of the RISK21 approach for Indigenous community-based human health risk assessments: two case studies - Katherine Chong; Madisan Chavez; Ave Dersch; John Doyle; Margaret Eggers; JoRee LaFrance; Myra J Lefthand; Findlay MacDermid; Claire McAuley; Vanessa Simonds; Sara L Young; Niladri Basu (FACETS)
Indigenous peoples in North America are disproportionately exposed to environmental contaminants and may face elevated health risks related to unique socio-cultural ties to the land. Conventional human health risk assessment (HHRA) methods do not account for these unique contexts. Regulators (i.e., Health Canada, US EPA) have called for the development of more ethical and efficient HHRA approaches, but to our knowledge no such approaches have been designed in consideration of Indigenous community contexts. RISK21 is a new HHRA approach gaining regulatory attention. We present two case studies piloting RISK21’s use in collaboration with three unique communities (Cold Lake First Nations, Chipewyan Prairie First Nation, Apsáalooke/Crow Nation). Our objectives are first, reflect upon the benefits and challenges of using RISK21 in these contexts; second, compare RISK21-based to conventional assessments; and third, ideate adaptations and improvements to the approach. The RISK21-based analyses had similar descriptive results to the original conventional assessments, including when using less information. We found RISK21 useful for rapid chemical assessment and visually representing data from multiple sources. We recommend areas where RISK21 (and other next-generation HHRA approaches) might be improved for Indigenous community contexts, including increasing the community relevance of communication tools and incorporating holistic and non-conventional information.